Long-term observations of feline meningoencephalitis of unknown etiology: clinical, CSF, and MRI findings - Yun, T; Koo, Y; Chae, Y; Lee, D; Park, J; Son, M; Kim, H; Yang, MP; Kang, BT (Journal of the Hellenic Veterinary Medical Society, 2023)
A 4-year-old neutered female Turkish Angora cat presented with acute onset of obtundation, right-sided head turn, and rolling. On neurologic examination, postural reactions were found either absent or decreased in all four limbs. Cranial nerve examination, such as menace response, pupillary light, and oculocephalic reflex, showed absent or decreased results. Magnetic resonance imaging (MRI) demonstrated demarcated lesions in the thalamus and brainstem, which were marked hyperintense on T2-weighted and FLAIR images and isointense on T1-weighted images. Cerebrospinal fluid (CSF) nucleated cell count was markedly elevated (258 cells/µl) with a neutrophilic pattern. The CSF polymerase chain reaction for infectious agents was negative. Based on these results, a diagnosed of feline meningoencephalitis of unknown etiology (FMUE) was made. The cat was treated with prednisolone (3 mg/kg, twice a daily), which was gradually tapered off. The follow-up of clinical signs, MRI, and CSF analysis was performed at 33, 118, and 611 days after the initial therapy. At 33 days, abnormalities of clinical signs, MRI, and CSF almost disappeared. At 139 days, because all examinations showed normal findings, the treatment was stopped. At 611 days, the final examinations showed no remarkable findings. This is the first case describing changes in the clinical signs, MRI findings, and CSF analysis of FMUE with long-term follow-up.